Realtime Monitoring System of Solar Panel Performance Based on Internet of Things Using Blynk Application - Inayatul Inayah; Nur Hayati; Aflah Nurcholis; Achmad Dimyati; Muhammad Ghofinda Prasetia (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2022)
Renewable energy is one of the options to meet the increasing energy needs. As a tropical country, Indonesia has great potential for solar energy development. At this time, solar panels have been built in places exposed to direct light. However, monitoring solar panels is still performed manually using a multimeter by operators or field officers, so it cannot be performed in real-time. Real-time tracking is carried out to prevent damage and decreased performance of solar panels. Hence, we designed a real-time solar panel monitoring system based Internet of Things (IoT) using the Blynk application on a smartphone. Based on the test between the measuring instrument and the Blynk application, the error percentage is 0.59% for voltage testing, 0.0001% for current testing, 1.03% for power testing, and 2.09% for temperature testing. A strong internet connection will significantly affect the performance of solar panels in real-time. This research is expected to monitor solar panel parameters remotely via a smartphone without having to come to the location and make it easier for users to monitor.